In Vitro Models Using the Human Placenta to Study Fetal Exposure to Drugs - Michal Kovo M.D., Ph.D; Abraham Golan (SAGE Publishing, 2008)
Over the recent years there has been a gradual rise in the use of pharmaceuticals during pregnancy. Knowledge on placental drug transfer and metabolism has increased during the past decades as well. Investigation of the transplacental transfer of any therapeutically useful drug is essential to the understanding of its metabolic processes and is a prerequisite for its use during pregnancy. The purpose of this review is to give insight on the various techniques that have been developed to evaluate transplacental transfer of drugs and xenobiotics.